A method for assessing the allocation of water volume in the water network tanks in the Podkarpackie Voivodeship using the Simpson index - Rak, Janusz; Stręk, Magdalena (Instal, 2023)
The collective water supply system belongs to the critical infrastructure of the cities functioning. This requires the safety of the water supply for consumption through the public water supply system. The basic elements in this area are the diversification of the number ofwater intakes in the supply subsystem and the allocation of water volume related to the number of tanks in the distribution system. Water in water supply tanks is stored when its amount supplied from the water treatment plant by the high lift pumping station exceeds the demand for water in a given city during the day, whereas it is taken at times when there is an increased demand for water in relation to the ability to supply it. This paper presents a method to evaluate water allocation in network water tanks according to the Edward H. Simpson index. The calculation of allocation ratios was presented for 11 selected cities in Poland. A five-stage categorization and a scale to assess the degree of water volume allocation in network water supply tanks were developed. On this basis, an assessment of the degree of allocation of water volume in network water supply tanks was made in the examined cities.